The influence of agents differentiating HL‐60 cells toward granulocyte‐like cells on their ability to release neutrophil extracellular traps - Manda‐Handzlik, Aneta; Bystrzycka, Weronika; Wachowska, Małgorzata; Sieczkowska, Sandra; Stelmaszczyk‐Emmel, Anna; Demkow, Urszula; Ciepiela, Olga (Immunology and cell biology, 2018)
Studies on neutrophil extracellular traps (NETs) are challenging as neutrophils live shortly and easily become activated. Thus, availability of a cell line model closely resembling the functions of peripheral blood neutrophils would be advantageous. Our purpose was to find a compound that most effectively differentiates human promyelocytic leukemia (HL‐60) cells toward granulocyte‐like cells able to release NETs. HL‐60 cells were differentiated with all‐trans retinoic acid (ATRA), dimethyl sulfoxide (DMSO) or dimethylformamide (DMF) and stimulated with phorbol 12‐myristate 13‐acetate (PMA) or calcium ionophore A23187 (CI). Cell differentiation, phagocytosis and calcium influx were analyzed by flow cytometry. Reactive oxygen species production and NETs release were measured fluorometrically and analyzed microscopically. LC3‐II accumulation and histone 3 citrullination were analyzed by western blot. ATRA most effectively differentiated HL‐60 cells toward granulocyte‐like cells. ATRA‐dHL‐60 cells released NETs only upon PMA stimulation, DMSO‐dHL‐60 cells only post CI stimulation, while DMF‐dHL‐60 cells formed NETs in response to both stimuli. Oxidative burst was induced in ATRA‐, DMSO‐ and DMF‐dHL‐60 cells post PMA stimulation and only in DMF‐dHL‐60 cells post CI stimulation. Increased histone 3 citrullination was observed in stimulated DMSO‐ and DMF‐, but not in ATRA‐dHL‐60 cells. The calcium influx was diminished in ATRA‐dHL‐60 cells. Significant increase in autophagosomes formation was observed only in PMA‐stimulated DMF‐dHL‐60 cells. Phagocytic index was higher in ATRA‐dHL‐60 cells than in control, DMSO‐ and DMF‐dHL‐60 cells. We conclude that ATRA, DMSO and DMF differentiate HL‐60 in different mechanisms. DMF is the best stimulus for HL‐60 cell differentiation for NETs studies. An aim of the study was to find a compound that most effectively differentiates HL‐60 (human promyelocytic leukemia) cells toward granulocyte‐like cells able to release NETs. HL‐60 cells were differentiated with all‐trans retinoic acid (ATRA), dimethyl sulfoxide (DMSO) or dimethylformamide (DMF) and stimulated with phorbol 12‐myristate 13‐acetate (PMA) or calcium ionophore A23187 (CI). ATRA‐dHL‐60 cells released NETs only upon PMA stimulation, DMSO‐dHL‐60 cells only post CI stimulation, while DMF‐dHL‐60 cells formed NETs in response to both stimuli.